Propulsion system integration and modelling synthesis - Christie, Robert (Cranfield University, 2016)
Concerns over fuel costs, along with the ever increasing requirement to reduce the impact of emissions, means that the world's airlines continue to introduce low-noise and more fuel-efficient aircraft into their fleet. Increasing the engine bypass ratio is one way to improve propulsive efficiency. However, historically an increase in the bypass ratio (BPR) has usually been associated with an increase in the fan diameter. Consequently, there can be a notable increase in the impact of the engine installation on the overall aircraft performance. For example, although the typical increase in fan diameter is generally beneficial to the uninstalled engine specific fuel consumption, the increase in the nacelle drag and weight are detrimental to the aircraft performance. There is also likely to be a stronger aerodynamic coupling between the engine and the airframe. Overall there is a risk that the gains in uninstalled engine performance are wholly or partly lost due to adverse engine-airframe installation and interference effects as well as additional nacelle weight. It is clear that the quantification of the elements of installation drag is a key aspect in the assessment of the likely developments in engine design as well as on the installation requirements for future airframe architectures. The overall aim of this research is to determine the effect of nacelle size, weight, geometry and installation on flight efficiency. This aim has been addressed through the development of a framework which combines the engine thermodynamic model, aircraft performance, engine installation aspects and a flight trajectory approach. This framework has been developed to assess the relative importance of various engine installation aspects on the overall flight fuel burn for a range of short-haul and long-haul configurations.